EARLY DIAGNOSIS AND SURGICAL TREATMENT OF DEEP PARAPROCTITIS IN DIABETIC PATIENTS - Kasimov, A.L.; Akhmadjonov, J.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Paraproctitis remains a significant surgical pathology, often complicated in the presence of systemic diseases such as diabetes mellitus (DM). Deep forms of paraproctitis in diabetic patients are characterized by atypical clinical manifestations, rapid progression of the infectious process, and a high risk of systemic complications. Early diagnosis and the selection of an adequate surgical approach are critical in improving outcomes for this vulnerable patient cohort. This review article summarizes the current literature and clinical experience regarding the diagnostic methods, classification systems, imaging modalities, and surgical tactics used in managing deep paraproctitis in patients with diabetes. Particular attention is paid to the peculiarities of wound healing, glycemic control, and perioperative management. Modern approaches, including minimally invasive drainage, staged surgery, and the role of antibacterial therapy, are discussed. The integration of a personalized treatment algorithm based on the severity of the inflammatory process, metabolic status, and comorbidity profile is emphasized as a promising direction in the optimization of care.